Vanadium Nitride/Porous Carbon Composites on Ni Foam for High‐Performance Supercapacitance. Issue 37 (25th October 2019) - Wang, Cong; Liang, Xizhuang; Wang, Zeyan; Liu, Yuanyuan; Wang, Peng; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Li, Yingjie; Huang, Baibiao
Abstract: A template‐free method for preparing vanadium nitride/carbon (VN/C) composites on Ni foam is developed by combining hydrothermal and nitridation methods. The VN/C composites on the Ni foam can be used as an electrode without any further treatment, and is found to be a good capacitance material. The highest specific capacitance of 386.6 F g −1 is obtained when the scan rate at 2 mV s −1, and the electrode demonstrates good cycling stability, owing to the synergistic integration of vanadium nitride with porous carbon, as well as the high surface area and conductive network provided by the microporous three‐dimensional Ni foam structure. Abstract : A self‐supported electrode consists of nitride and carbon prepared by combining hydrothermal and nitridation methods can be used directly for electrochemical performance test. The results show that VN/C composite can be used as a substitute material for supercapacitors in high‐power devices.